2003
DOI: 10.1002/anie.200390114
|View full text |Cite
|
Sign up to set email alerts
|

Thioglycoligases: Mutant Glycosidases for Thioglycoside Synthesis

Abstract: Engineering of the active site of retaining glycosidases in conjunction with the appropriate modification of their substrates has led to the enzymatic synthesis of thioglycosidic linkages in thiooligosaccharides (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(93 citation statements)
references
References 28 publications
1
88
0
2
Order By: Relevance
“…Such a mechanism in which the ''base'' residue is tailored to match the pK a of the acceptor is not without precedent. Studies with mutant glycosidases have shown that removal of the charged base engineers acceptance of nonnatural sulfur-containing acceptors in transglycosylation reactions (22). It may also be relevant that the two characterized cytokinin-N-glycosyltransferases in Arabidopsis (UGT76C2 and UGT76C1) are rare examples of UGTs that do not have, based on sequence alignments, a histidine at the ''base'' position.…”
Section: Discussionmentioning
confidence: 99%
“…Such a mechanism in which the ''base'' residue is tailored to match the pK a of the acceptor is not without precedent. Studies with mutant glycosidases have shown that removal of the charged base engineers acceptance of nonnatural sulfur-containing acceptors in transglycosylation reactions (22). It may also be relevant that the two characterized cytokinin-N-glycosyltransferases in Arabidopsis (UGT76C2 and UGT76C1) are rare examples of UGTs that do not have, based on sequence alignments, a histidine at the ''base'' position.…”
Section: Discussionmentioning
confidence: 99%
“…tumor growth, progression and spread. Within this quest, thioglycosides attract attention as potential drug leads due to their stability against hydrolysis [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…These in turn can be used as carbon or energy sources for microorganisms and higher animals. Hemicellulases have attracted much attention in recent years because of their potential industrial uses in biobleaching of paper pulp (2,3), bioconversion of lignocellulose material to fermentative products (4), improvement of animal feedstock digestibility, and recently in the field of oligosaccharide and thioglycoside synthesis (5,6).…”
mentioning
confidence: 99%